Effects of current reproductive success and individual heterogeneity on survival and future reproductive success of female Wood Ducks. (25th May 2016) - Kennamer, Robert A.; Hepp, Gary R.; Alexander, Bradley W.
Abstract: Estimates of vital rates and their sources of variation are necessary to understand the population dynamics of any organism. These data have been used to test predictions of life history theory as well as to guide decisions of wildlife managers and conservation biologists. Life history theory predicts tradeoffs among life history traits, such that current reproductive effort will be negatively correlated with survival and/or future reproduction. Many studies support this prediction, but others report positive covariation between fitness traits, and attribute positive correlations to differences in individual quality. In this study, we used 11 yr of capture–mark–recapture data of breeding female Wood Ducks ( Aix sponsa ), along with their breeding histories, to examine sources of variation in annual survival rates and to assess the impact of current reproductive success on probabilities of survival and future reproductive success. Cormack-Jolly-Seber models indicated that apparent survival of female Wood Ducks did not vary annually and was only weakly affected by age class and breeding habitat conditions, but that there was a strong positive relationship between survival and the number of successful nests (0, 1, or 2). Next, we used a multistate analysis to examine the importance of female nest fate (successful or failed) on the probability of surviving and of nesting successfully the next year. Early incubation body mass was used to assess the nutritional status and quality of females. Females that nested successfully in year t were not less likely to nest successfully in year t + 1 than females that had nested unsuccessfully in year t . We also found strong positive covariation between nest success in year t and the probability of surviving. However, being in relatively good or poor condition had no effect on these relationships. Our results are consistent with the idea that female quality is heterogeneous, but body mass was not a good proxy of quality. Therefore, the existence of tradeoffs between female reproductive success and survival or future reproduction was less clear because of our inability to identify and control for differences in female quality.